The Effect of Ginger Compress on Back Pain in Pregnant Women in the Work Area of X Health Center, Cianjur Regency, Indonesia - Friska, Deka (HM Publisher, 2024)
Back pain is one of the disorders often experienced by pregnant women. The research results show that the prevalence of back pain in pregnant women in Indonesia reaches 60-80%. One non-pharmacological therapy that can be used to treat back pain in pregnant women is a ginger compress. This study aims to determine the effect of ginger compresses on back pain in third-trimester pregnant women in the working area of X Health Center, Cianjur Regency, Indonesia. This study used a quasi-experimental design with a two-group pretest-posttest design. The research population was pregnant women in the third trimester who experienced back pain. The sample size was 60 people, who were divided into two groups, namely the intervention group (30 people) and the control group (30 people). The intervention group was given a ginger compress for 15 minutes, 3 times a day, for 3 days. The control group was given warm water compresses for 15 minutes, 3 times a day, for 3 days. The results of the study showed that the average value of back pain in the intervention group before the intervention was 4.68 (moderate pain scale) and after the intervention was 2.91 (mild pain scale). The average value of back pain in the control group before the intervention was 4.75 (moderate pain scale), and after the intervention, it was 3.88 (moderate pain scale). The Wilcoxon test showed that ginger compresses reduced back pain in third-trimester pregnant women (p=0.000). The conclusion of this study is that ginger compresses have an effect on reducing back pain in third-trimester pregnant women.